Babesia microti: Pathogen Genomics, Genetic Variability, Immunodominant Antigens, and Pathogenesis - Puri, Ankit; Bajpai, Surabhi; Meredith, Scott; Aravind, L.; Krause, Peter J.; Kumar, Sanjai (Frontiers in Microbiology, 2021)
More than 100 Babesia spp. tick-borne parasites are known to infect mammalian and avian hosts. Babesia belong to Order Piroplasmid ranked in the Phylum Apicomplexa. Recent phylogenetic studies have revealed that of the three genera that constitute Piroplasmida, Babesia and Theileria are polyphyletic while Cytauxzoon is nested within a clade of Theileria. Several Babesia spp. and sub-types have been found to cause human disease. Babesia microti, the most common species that infects humans, is endemic in the Northeastern and upper Midwestern United States and is sporadically reported elsewhere in the world. Most infections are transmitted by Ixodid (hard-bodied) ticks, although they occasionally can be spread through blood transfusion and rarely via perinatal transmission and organ transplantation. Babesiosis most often presents as a mild to moderate disease, however infection severity ranges from asymptomatic to lethal. Diagnosis is usually confirmed by blood smear or polymerase chain reaction (PCR). Treatment consists of atovaquone and azithromycin or clindamycin and quinine and usually is effective but may be problematic in immunocompromised hosts. There is no human Babesia vaccine. B. microti genomics studies have only recently been initiated, however they already have yielded important new insights regarding the pathogen, population structure, and pathogenesis. Continued genomic research holds great promise for improving the diagnosis, management, and prevention of human babesiosis, and in particular, the identification of lineage-specific families of cell-surface proteins with potential roles in cytoadherence, immune evasion and pathogenesis.